They Still Have a Dream: a research paper on the emergence of the BLM movement as a consequence of racial profiling by police force and the reproduction of racist messages in mass media - López Russomanno, María Sol; Malomo Menelle, Laura; Piemontese, Josefina (Bridging Cultures, 2022)
This academic paper focuses on the racial profiling and discursive bias against African American people in the United States. The aim of this paper is twofold: first, to illustrate and develop the Black Lives Matter movement as a consequence of racism as well as the legislation and different programs that have been created to reduce police brutality and, second, to evince the way mass media reproduces and perpetrates racist messages. This academic paper was written by means of collecting information retrieved from varied sources and assorted experts of each area mentioned as well as by applying the discursive strategies proposed by linguist Van Dijk. Ultimately, the authors of this work concluded that structural racism is a trait that prevails in the American society in spite of the creation of social movements and regulations that aim to combat racial profiling.